Implementasi model pembelajaran berbasis proyek (project based learning) untuk meningkatkan aktivitas dan hasil belajar siswa - Martina Lona Jusita (Universitas Negeri Malang, 2019)
Project-based Learning models provide opportunities for the teacher to manage learning improving project work. Students required to solve problems by applying the skills of researching, analysing, making, and presenting learning products based on real experience. The implementation of a project-based learning model has successfully increased learning activities and outcomes. Evidently from each cycle showed a significant increase. In the first cycle high learning activities were only 12 students (37.50%) with a success rate of 58 in sufficient categories and a mean of 65 learning outcomes. The second cycle of learning activities increased to 22 students (68.75%) with 71 succes rate in good categories and the average learning outcomes are 76. In the third cycle high learning activities reached 26 students (81.25%) with an 80 level of success in the good category and the average learning outcomes 81. The results of this action research reinforce the theoretical and empirical study of the effectiveness of PBL to improve activities and learning outcomes on material with characteristics at the analyzing level.DOI: 10.17977/um022v4i22019p090